Hunter-gatherers and early food producing societies in Northeastern Africa - Kabaciński, Jacek ca. 20./21. Jh; Chłodnicki, Marek 1955-; Kobusiewicz, Michał 1939-2024 (Propylaeum, 2017)
archaeology - hunter-gatherers - early food producing societies - Northeastern Africa